2016
DOI: 10.21873/anticanres.11264
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Cytoplasmic CD24 Expression Is Associated with Malignant Transformation but Favorable Prognosis of Colorectal Adenocarcinoma

Abstract: (I to III versus IV) (p=0.005, p=0.034, and p=0.006, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Immunohistochemical staining of the tissue sections from the TMA paraffin blocks was performed as previously described (12). A primary rabbit polyclonal antibody against human CYP4F2 (ab111741, diluted 1:100; Abcam, Cambridge, UK) was used; the reactions were incubated at room temperature for 1 h. A modified Allred et al (13) method was applied to evaluate both the intensity of the immunohistochemical staining and the proportion of stained neoplastic or non-neoplastic hepatocytes on each slide.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining of the tissue sections from the TMA paraffin blocks was performed as previously described (12). A primary rabbit polyclonal antibody against human CYP4F2 (ab111741, diluted 1:100; Abcam, Cambridge, UK) was used; the reactions were incubated at room temperature for 1 h. A modified Allred et al (13) method was applied to evaluate both the intensity of the immunohistochemical staining and the proportion of stained neoplastic or non-neoplastic hepatocytes on each slide.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining of the tissue sections from the tissue microarrays paraffin blocks was performed as previously described . A primary rabbit polyclonal antibody to human CYP4A11, which is homologous to human CYP4A11 (product # PA5‐30004, diluted 1:100; Thermo Fisher Scientific, Rockford, IL, USA), was used; the reactions were incubated at room temperature for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…Its expression was confirmed in normal nervous tissue [16] and in cancers of the colon [5], pancreas [24], breast, and prostate [26]. CD24 is involved in cellular signaling processes, in cellular differentiation, and in proliferation and is being considered a significant marker of cancer stem cells (CSCs) [4,16,39]. The mechanism by which CD24 participates in signaling processes seems to be related to mitogen-activated protein kinase (MAPK) and serine/threonine pathway [26].…”
Section: Cd24 In Colon Cancermentioning
confidence: 99%
“…CD44 is involved in first steps of carcinogenesis and plays an important role in liver metastasis formation [4,9,[41][42][43]. Yeo et al found CD24 a useful diagnostic marker of early colon cancer [39], whereas its expression was higher in malignant polyps than CD24 expression in colon adenomatous lesions.…”
Section: Cd24 In Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation